Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/ls.133
|View full text |Cite
|
Sign up to set email alerts
|

Herringbone‐grooved bearing with non‐uniform grooves for high‐speed spindle

Abstract: A hydrodynamic bearing with non-uniform herringbone grooves has been developed for use with highspeed motor spindles. The grooves gradually become narrower, shallower and less straight (curved) towards the herringbone centre along axial direction, resulting in an increased pumping effect of the spiral grooves. The optimum dimensions of the grooves for increasing the critical bearing number were clarifi ed theoretically, and bearings with non-uniform herringbone grooves were found to increase the critical beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Ikeda et al. 19 experimentally found that the hydrodynamic bearing with nonuniform herringbone grooves increased the maximum rotational speed of high-speed spindles by about 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Ikeda et al. 19 experimentally found that the hydrodynamic bearing with nonuniform herringbone grooves increased the maximum rotational speed of high-speed spindles by about 20%.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the bearing strongly depends on the groove configurations. Therefore, many papers concerning optimal herringbone groove configurations were already published [10][11][12][13]. However, few papers discussed the stability of the bearings with viscoelastic supports.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzed film lubrication of Herringbone grooves by two-dimensional that ignored the narrow groove theory shown that light-load herringbone groove lubricating bearings had better stable. The research on herringbone groove lubricating bearing's parameters effected on the characteristics of lubrication and rotor dynamic, shown that pressure distributed widely along the circumference and the rotor had higher stable [6,7]. This paper numerical analysis [8] of herringbone groove hydrodynamic lubricating bearing based on Reynolds equation [9], obtained the high speed and small herringbone groove hydrodynamic lubricating bearing's relationship between load, rotational speed and eccentricity, temperature rise which provided evidences for application.…”
Section: Introductionmentioning
confidence: 99%